Tectonomagmatic evolution of the Early Ordovician suprasubduction-zone ophiolites of the Trondheim Region, Mid-Norwegian Caledonides - Slagstad, T.; Pin, C.; Roberts, D.; Kirkland, Chris; Grenne, T.; Dunning, G.; Sauer, S.; Andersen, T. (Geological Society Publishing House, 2014)
The Trondheim Region ophiolites in the Mid-Norwegian Caledonides represent variably tectonized ophiolite fragments. We present high-precision thermal-ionization mass spectrometry and secondary-ion mass spectrometry (SIMS) U–Pb zircon dates, whole-rock geochemical and Sm–Nd data and Lu–Hf zircon analyses that permit the timing and nature of various stages in the evolution of the ophiolite to be elucidated. Plagiogranite intrusions dated at 487 and 480 Ma have relatively juvenile Nd and Hf isotopic compositions (eNd(t)=6.3, eHf(t)=8.2–12.4). Geochemical data indicate a subduction-zone influence, suggesting formation in an oceanic back-arc setting. At 481 Ma, a granitoid body with a relatively strong unradiogenic Nd and Hf isotopic composition (eNd(t)=-2.6 to -4.0, eHf(t)=3.8–6.4) and subduction-zone geochemical signature intruded the ophiolite. We interpret this stage to reflect the formation or migration of an oceanic arc above a subduction zone influenced by continentally derived sediments. At c. 475–465 Ma, a greenstone-dominated conglomerate and volcaniclastic sequence was deposited on the eroded ophiolite, indicating obduction between about 480 and 475 Ma. At c. 468–467 Ma, the deformed ophiolite and its sedimentary cover was intruded by trondhjemite dykes and shoshonitic volcanic rocks with intermediate Nd and Hf isotopic compositions (eNd(t)=3.0–3.9, eHf(t)=4.4–10.2). We interpret this magmatism to reflect subduction-polarity reversal and establishment of a magmatic arc at the continental margin shortly after obduction.